The Cost-Effectiveness of Treatment Modalities for Ureteral Stones - Justin Ji-Yuen Siu MD; Huey-Yi Chen MD, PhD; Po-Chi Liao MD; Jen-Huai Chiang MS; Chao-Hsiang Chang MD; Yung-Hsiang Chen PhD; Wen-Chi Chen MD, PhD (SAGE Publishing, 2016)
Additional intervention and medical treatment of complications may follow the primary treatment of a ureteral stone. We investigated the cost of the treatment of ureteral stone(s) within 45 days after initial intervention by means of retrospective analysis of the National Health Insurance Research Database of Taiwan. All patients of ages ≥20 years diagnosed with ureteral stone(s)( International Classification of Diseases, Ninth Revision, Clinical Modification/ICD-9-CM: 592.1) from January 2001 to December 2011 were enrolled. We included a comorbidity code only if the diagnosis appeared in at least 2 separate claims in a patient's record. Treatment modalities (code) included extracorporeal shock-wave lithotripsy (SWL; 98.51), ureteroscopic lithotripsy (URSL; 56.31), percutaneous nephrolithotripsy (PNL; 55.04), (open) ureterolithotomy (56.20), and laparoscopy (ie, laparoscopic ureterolithotomy; 54.21). There were 28 513 patients with ureteral stones (13 848 men and 14 665 women) in the randomized sample of 1 million patients. The mean cost was 526.4 ± 724.1 United States Dollar (USD). The costs of treatment were significantly increased in patients with comorbidities. The costs of treatment among each primary treatment modalities were 1212.2 ± 627.3, 1146.7 ± 816.8, 2507.4 ± 1333.5, 1533.3 ± 1137.1, 2566.4 ± 2594.3, and 209.8 ± 473.2 USD in the SWL, URSL, PNL, (open) ureterolithotomy, laparoscopy (laparoscopic ureterolithotomy), and conservative treatment group, respectively. In conclusion, URSL was more cost-effective than SWL and PNL as a primary treatment modality for ureteral stone(s) when the possible additional costs within 45 days after the initial operation were included in the calculation.